Progressive bulbar symptomatology due to vascular brainstem compression. Issue 3 (15th March 2021) - Younus, Osman; Hampton, Timothy; Silber, Eli; Dervenoulas, George
Abstract : Symptomatic brainstem compression from vertebral artery dolichoectasia is rare. There are no recognised diagnostic or treatment criteria to guide management of this disease. We report a case of medullary compression and cerebral ischaemia from an enlarged and tortuous vertebral artery. Our patient developed progressive dysphonia and dysphagia. Cerebral MRI revealed compression of the medulla oblongata by a right ectatic vertebral artery and a right occipital lobe infarct. Other causes of bulbar dysfunction were ruled out. He was treated with anticoagulation and underwent percutaneous endoscopic gastrostomy. We review selected literature on the presentation, diagnosis and management of this rare neurologic condition.